2021
DOI: 10.3390/foods10112833
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Properties of Coix Seed Oil against HT-29 Colon Cells through Regulation of the PI3K/AKT Signaling Pathway

Abstract: This study aims to observe the effects of coix seed oil (CSO) on HT-29 cells and investigate its possible regulation mechanism of the PI3K/Akt signaling pathway. Fatty acid analysis showed that coix seed oil mainly contains oleic acid (50.54%), linoleic acid (33.76%), palmitic acid (11.74%), and stearic acid (2.45%). Fourier transform infrared results found that the fatty acid functional groups present in the oil matched well with the vegetable oil band. The results from CCK-8 assays showed that CSO dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…It can be used for hyperlipidemia by reducing blood lipids and exerting antioxidant effects [37]. In addition, CSO is reported to show anticancer effects in preclinical models of sarcoma [38], lung cancer [39], pancreatic cancer [40], liver cancer [41], breast cancer [42], and colon cancer [43]. CSO is shown to be clinically effective [44], and it also helps cancer patients by relieving pain induced by cancer [45].…”
Section: Coix Seed Oil (Cso)mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be used for hyperlipidemia by reducing blood lipids and exerting antioxidant effects [37]. In addition, CSO is reported to show anticancer effects in preclinical models of sarcoma [38], lung cancer [39], pancreatic cancer [40], liver cancer [41], breast cancer [42], and colon cancer [43]. CSO is shown to be clinically effective [44], and it also helps cancer patients by relieving pain induced by cancer [45].…”
Section: Coix Seed Oil (Cso)mentioning
confidence: 99%
“…Plums abundantly contain various bioactive components such as polyphenols, chlorogenic acid, rutin, and caffeic acid, and so they are considered "superfoods" that can benefit health [42]. Dried plums show anticancer effects in human hepatocellular carcinoma [43] and anti-inflammatory effects in experimental arthritis [44]. Alsolmei et al reported that dried plum extract could prevent cancer-induced damage in C2C12 muscle cells [45].…”
Section: Prunus Domestica Lmentioning
confidence: 99%
“…Studies have shown that the injection of Kanglaite, a patented Chinese medicine developed from Coix seed oil as the raw material, induces a good therapeutic response in the treatment of gastric, colorectal, and lung cancers, among others. Some studies have also discussed its mechanism of action, demonstrating that the fatty acids and esters in Coicis Semen can exert anti-tumor effects by inhibiting the proliferation and metastasis of tumor cells (Xiong et al, 2018;Lin et al, 2019;Ni et al, 2021), preventing tumor angiogenesis (Zhang, 2020), increasing the sensitivity to radiotherapy (Liu J. et al, 2018), and improving the body's immunity (Zhang, 2017).…”
Section: Phytochemistry Of Coicis Semenmentioning
confidence: 99%
“…On the HT-29 colon cancer cell model, the anticancer effect of Coix seed oil is dose-dependent and time-dependent. With the increase of drug concentration and the passage of time, the survival rate of tumor cells will also decrease[ 40 ]. The synergistic effect of paclitaxel treatment after pretreatment with KLT is the best, and KLT inhibits nuclear factor NF-κΒ and upregulates the expression of connexin 43, making cancer cells sensitive to paclitaxel[ 41 ], thereby exerting an inhibitory effect on colon cancer cells.…”
Section: The Anti-tumor Effect Of Coix Seedmentioning
confidence: 99%